Association between RAD51 135 G/C polymorphism and risk of 3 common gynecological cancers: A meta-analysis. Issue 26 (June 2018) - Zeng, Xianling; Zhang, Yafei; Yang, Lei; Xu, Huiqiu; Zhang, Taohong; An, Ruifang; Zhu, Kexiu
Abstract: Aim: Available data concerning the association between RAD51 135G/C (rs1801320) polymorphism and the risk of 3 common gynecological cancers still could not reach a consensus. Thus, we conducted a meta-analysis to explore the relationship. Methods: Several electronic databases and bibliographies of relevant articles were screened to identify the studies up to July 2017. Then a meta-analysis was performed to evaluate the connection between 3 common gynecological tumors' susceptibility and RAD51 135G/C polymorphism in different inheritance models. Simultaneously, we did subgroup analysis and sensitivity analysis if necessary. Results: A total of 11 articles including 14 studies involving 4097 cases and 5890 controls were included in this meta-analysis. Overall, RAD51 135G/C polymorphism increased the risk of 3 common gynecological tumors. The subgroup analysis stratified by cancer types- endometrial carcinoma (EC) and ovarian cancer (OC)-showed that RAD51 135G/C polymorphism increased the risk of EC: allele model (C vs G: odds ratio [OR] = 4.32, 95% confidence interval [CI] = 2.63–7.10, P < .00001), dominant model (CC + GC vs GG: OR = 2.28, 95% CI = 1.44–3.60, P = .004), recessive model (CC vs GC + GG: OR = 10.27, 95% CI = 14.71–22.38, P < .00001), and homozygous model (CC vs GG: OR = 7.26, 95% CI = 3.59–14.68, P < .00001), but there was no significant association between RAD51 135G/C polymorphism and OC. In the subgroup analysis stratified by source of controls, a significantly increased risk was observed in hospital-based studies. Nevertheless, the data showed RAD51 135G/C polymorphism had no link in population-based studies. Conclusions: This meta-analysis suggested that RAD51 135G/C polymorphism was a risk factor for the three common gynecological tumors, especially for EC among hospital-based populations.